Danish Cattle Farmers' Experience With Fitness for Transport – A Questionnaire Survey - Dahl-Pedersen, Kirstin (Frontiers in Veterinary Science, 2022)
Worldwide, cattle are transported in great numbers for breeding, fattening and slaughter. Within the European Union, the Council Regulation 1/2005 states that all animals must be fit for transport. Yet, the line between fit and unfit is blurred as the regulation allows for animals that are slightly ill or injured to be transported. However, “slightly ill or injured” lack a clear definition leaving room for individual interpretation of fitness for transport with potential negative implications in terms of both animal welfare and legal certainty. The aim of the present study was to gain an understanding of cattle farmers' experience with and doubt about assessment of fitness for transport-a topic that has received limited scientific attention, despite the important role of farmers in maintaining acceptable animal welfare during transport. The results of the study are based on 119 Danish cattle farmers' answers to a questionnaire survey. The majority of respondents felt they possessed the knowledge and skills required for assessment of fitness for transport. However, a considerable large part of the respondents, one third approximately, reported to be in doubt at least sometimes and likewise one third felt a lack of knowledge at least sometimes. In addition, more than half of the respondents reported that they at least sometimes found it difficult to understand the rules to address the disconnect between on-farm and slaughterhouse decisions and fitness for on-farm slaughter. These results indicate that learning materials, assessment tools and training programs could be helpful for a large group of cattle farmers in order to secure animal welfare during transport. The results also underline the need for further research to clarify what constitutes a “fit” vs. “unfit” animal.